An Introduction and Mission of Building Bridges to Reach the Unknown - Houran, James (Journal of Scientific Exploration, 2022)
The founding of the Journal of Scientific Exploration in 1987 coincided with my graduation from high school and start of higher education. Even then I was deeply interested in all types of anomalies thanks to my parents’ gift about ten years earlier of Jane Werner Watson and Sol Chaneles’ (1976) The Golden Book of the Mysterious (NY: Golden Press). That book was a childhood obsession that steadily evolved to serious academic curiosity, which then quickly transformed into passionate participation in scholarly research and writing. My curiosity and passion certainly endure, but these have been become increasingly balanced with skepticism that erupted from several negative experiences over the years with ideological-motivated academics. Of course, bias cuts both ways (Drinkwater et al., 2019; Irwin et al., 2016, 2017; Kennedy, 2005; Truzzi, 1987), so my own work has disappointed — and sometimes even irked — both debunkers of the paranormal and fervent believers in otherworldly phenomena. My appointment as the new Editor-in-Chief (EiC) might thus surprise individuals who do not view me as a sympathetic champion for the advancement of ‘edge science,’ or what amounts to empirical observations that challenge scientific principles or concepts as presently understood. This Editorial avoids reciting my professional background and interests, which anyone can easily read at the Parapsychological Association website (https://parapsych.org/users/jhouran/profile.aspx) or via my ORCID record (https://orcid.org/0000-0003-1725-582X). Rather, the goal here is to introduce readers to the underlying philosophy that will be the backbone of my JSE tenure. Indeed, readers deserve to know what the EiC stands for. I have also not been immersed in the Society for Scientific Exploration’s (SSE) activities and culture in recent years, so some members might understandably deem me an outsider. However, my academic career has consistently centered on edge science and advancing its cause. The diligent efforts of past Editors, Associate Editors, Editorial Board, and the unsung hero known as Kathleen Erickson (Managing Editor) have achieved notable strides in the JSE’s quality and impact over the years. But my primary aim is now to take the journal to the next level by bolstering its familiarity, reach, and influence within academia and the mainstream consciousness alike. This pursuit involves diversifying the provocative research in its pages and making that content more accessible and useful to non-specialists in other fields, as well as to journalistic outlets and the mass media. The latter forums can and should play a valuable role in public science education (Höttecke & Allchin, 2020; Huber et al., 2019; Olson & Kutner, 2008), although these can easily miss the mark as illustrated by my own frustrating experiences with misreported research.